Hubungan Asupan Serat, Konsumsi Air Putih, Aktivitas Fisik, dan Jenis Kelamin dengan Kejadian Konstipasi Fungsional pada Siswa/ Siswi SMA Negeri 1 Praya Timur, Lombok Tengah - Wahyu Rizal, Muhamad; Ruqayyah, Siti; Prajitno, Sugianto; Mahdaniyati, Aulia (Jurnal Ilmiah Wahana Pendidikan, 2024)
Background: Constipation is a condition in which a person has difficulty in defecating characterized by a solid consistency of feces and the defecation frequency is equal to or more than once every three days. Generally, constipation is classified into two types: constipation due to structural abnormalities and functional constipation. The later type basically caused by poor life styles such as low fiber intake, low fluid intake, low physical activity and high level of stress. Objective: Analyzing the relationship between fiber intake, water consumption, physical activity, and gender with the incidence of functional constipation. Method: The research used quantitative analytical observational methods along with a cross sectional research design. The data was collected in one day in which the respondents were gathered in one room and divided into three sessions. Meanwhile, the proportionate stratified random sampling was employed with 100 respondents. Additionally, Spearman rank correlation test was utilized with a significant value limit of (p-value) < 0.05. Results: The research shows that the majority of the respondents were aged 15 years (15%) and 61 % of the respondent had functional constipation. Furthermore, the research indicates that the participants also had low fiber intake, low water consumption, and low physical activity accounted for 61%, 62% and 42% respectively. The study also shows that the dominant gender was female outnumbered the male one for 68%. Meanwhile, Bivariate analysis illustrates that there is a relationship between functional constipation and all the variables (p=0.000) – fiber intake, water consumption, physical activity and gender. Conclusion: Fiber intake, water consumption, physical activity, and gender are closely related with functional constipation.